#TITLE_ALTERNATIVE# - EKA PUTRI (NIM : 10213048), TENISA
Source Scanning Algorithm (SSA) is new method for imaging the distribution of seismic source by using trial locations and origin time principle. This method use the arrival time and amplitude of seismic waves in each stations. Data of arrival time and amplitude is processed and converted into data of brightness. The point that show maximum brightness value is a seismic source (hypocenter) location. SSA method does not require the process of picking phase so there will be no error in determining the arrival time as in picking phase method. This method is effective to determining the seismic source location even in multiple events and high noise condition. Distribution of seismic source can show the flow pattern of reinjection fluid or fault dynamics in geothermal field. In this research, the determination of hypocenter point using synthetic data and observation data of U geothermal field. For synthetic data, the determination of hypocenter point with a variety of conditions the number of stations, the number of hypocenter, the number of weighting factor, and different noise levels. For observation data, there were 4 stations that record microearthquake in this area. The data was collected for 24 days from 17 March 2015 to 11 April 2015 and recorded 16 events. After data processing is complete, we will get hypocenter point which is a grid with maximum brightness value. This hypocenter point can be seen from various Plane, XY Plane (top view), YZ Plane (side view), and XZ Plane (front view). All hypocenter points are plotted in 3D space to determine the fluid flow in reservoir. Hypocenter distribution tends to move southward indicating that the fluid also tends to move southwards following the fracture directiction.